Development of Smart Clay Pottery Integrated with IoT to Extend the Shelf Life of Fruits and Vegetables - Darwanto, Agus; Nurus Shillah, Annisa; Salsabila, Talitha Aulia Zuriah (Bincang Sains dan Teknologi, 2025)
Fruits and vegetables have relatively short shelf lives, necessitating storage solutions such as refrigerators to maintain freshness. However, not all types of fruits and vegetables are suitable for refrigeration, and not all vendors have access to refrigerators or space to accommodate them. This study aims to develop an eco-friendly alternative storage medium using clay pottery enhanced with zeolite and activated charcoal to extend the shelf life of fruits and vegetables. The freshness levels were monitored using TGS 2600, MQ3, MQ4, MQ2, and MQ8 sensors connected to smartphones through an Internet of Things (IoT) platform and supported by an artificial intelligence-based chatbot. This quantitative descriptive research employed experimental methods with samples consisting of spinach (Ipomoea aquatica), mangoes (Mangifera indica), and bananas (Musa spp.). Each produce item was stored in treated clay pottery (with zeolite and activated charcoal), untreated clay pottery, and a refrigerator (control). Observations were conducted over five days, evaluating parameters such as texture, color, and aroma. Six expert respondents assessed the samples using a Likert scale. Data were analyzed using ANOVA and Duncan’s Multiple Range Test (DMRT). The findings indicate that the treated pottery significantly improved the shelf life of fruits and vegetables compared to untreated pottery and refrigeration. Sensor-based monitoring integrated with solar-powered panels and the Blynk application, supported by cloud storage and AI-driven chatbot communication, enabled real-time assessment and user interaction. This research demonstrates that innovative clay storage systems, enhanced with natural absorbents and digital technologies, offer a sustainable and effective method for preserving perishable produce.